2003
DOI: 10.1021/ie0301233
|View full text |Cite
|
Sign up to set email alerts
|

Lycopene and β-Carotene Extraction from Tomato Processing Waste Using Supercritical CO2

Abstract: Tomato skins and their mixtures with seeds were submitted to supercritical CO 2 extraction using a flow apparatus at pressures of 250 and 300 bar and temperatures of 60 and 80°C. Two different mean particle sizes (80 and 345 µm) were used at two solvent flow rates (0.792 and 1.35 kg/h). The yields of lipids, lycopene, and -carotene obtained by supercritical fluid extraction were compared with those obtained by conventional organic solvent extraction. Supercritical fluid extraction from tomato skins at 300 bar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
105
0
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(113 citation statements)
references
References 22 publications
5
105
0
3
Order By: Relevance
“…[196][197][198][199][200][201][202][203][204][205] β-Carotene and lycopene have numerous health benefits, the latter having antioxidant and anti-cancer properties. 196,198 Winemaking is also a source of different wastes that can potentially be valorised. ScCO 2 (with and without a modifier) extractions of by-products from the wine industry have also been investigated, and catechin and other phenolic compounds were successfully isolated from grape seeds with higher yields when compared to traditional solid-liquid extraction.…”
Section: Supercritical Carbon Dioxide Extraction Subcritical Water Ementioning
confidence: 99%
“…[196][197][198][199][200][201][202][203][204][205] β-Carotene and lycopene have numerous health benefits, the latter having antioxidant and anti-cancer properties. 196,198 Winemaking is also a source of different wastes that can potentially be valorised. ScCO 2 (with and without a modifier) extractions of by-products from the wine industry have also been investigated, and catechin and other phenolic compounds were successfully isolated from grape seeds with higher yields when compared to traditional solid-liquid extraction.…”
Section: Supercritical Carbon Dioxide Extraction Subcritical Water Ementioning
confidence: 99%
“…Recently, previous studied reported that the waste product of tomato or tomato pomace obtained from food industry processing contained skin, pulp and crushed seeds of tomato were still contains lycopene and betacarotene (Sabio et al, 2003). It had been reported that dried tomato pomace exhibited cognitive enhancing effect in normal and cognitive impairment conditions (Thukhammee et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Nas últimas duas décadas houve nítida intensificação de pesquisas envolvendo carotenóides, tendo este segmento recebido considerável atenção por parte de profissionais de diferentes áreas do conhecimento, tais como químicos orgânicos, químicos de alimentos, biólogos, médicos e ambientalistas 12 . Além da crescente busca por produtos que contenham em sua formulação compostos naturais 24,26 , o interesse pelos carotenóides se justifica tendo em vista que tais compostos têm sido propostos como agentes de ação preventiva ao câncer, inibidores de úlceras, rejuvenescedores, inibidores de ataques do coração 3,5,8,14,16 , bem como têm sido utilizados na imunização e inseminação artificial do gado 4,9 .…”
Section: Introductionunclassified
“…Além da crescente busca por produtos que contenham em sua formulação compostos naturais 24,26 , o interesse pelos carotenóides se justifica tendo em vista que tais compostos têm sido propostos como agentes de ação preventiva ao câncer, inibidores de úlceras, rejuvenescedores, inibidores de ataques do coração 3,5,8,14,16 , bem como têm sido utilizados na imunização e inseminação artificial do gado 4,9 .…”
Section: Introductionunclassified
See 1 more Smart Citation